Upper Gastrointestinal Bleeding In Children - Hassoon, Abdullah J.; AlMaeeni, Afrah A.; Matloub, Huda Y. (Journal of the Faculty of Medicine Baghdad, 2012)
BACKGROUND:Gastrointestinal bleeding (GIB) in infants and children is one of the more alarming conditions encountered in pediatrics. It is nonetheless an anxiety-provoking complaint. Most etiologies are self-limited and benign.AIM OF STUDY:To review the causes of upper gastrointestinal bleeding and its clinical presentations in children and evaluate the role of endoscopy for diagnostic and therapeutic purposes.PATIENTS AND METHOD:Fifty eight patients from 4 days old up to the age of 18 years who referred with upper gastrointestinal bleeding to the Gastro intestinal&Hepatology unit in the Children Welfare Teaching Hospital/ Medical City/Baghdad, in the period from 1st of April 2010 to 1st of November 2010.RESULTS: there were 58 patients (34 males and 24 females) with male to female ratio (1.4:1), 58.5% presented with hematemesis, 5.2% had melena and 31.1% had both, 5.2% of patients presented with hematochezia . The most common causes of upper GI bleeding among all patients were esophageal varices (39%), gastric erosions (19.6%), duodenal ulcer (7.4%), gastric ulcer (9.7%), (4.9%) for Mallory Weiss syndrome and also (4.9%) for oesophagitis. The causes of bleeding could not be ascertained in (30%) of cases. (15.3%) of patients, there was a history of consumption of medications predisposing them to upper GI bleeding. Fifteen patients (25.8 %) had comorbid disease. There were three deaths (5.1%) in this study.CONCLUSION: oesophagealvarices were the common cause of upper GI bleeding. Most patients presented with hematemesis. In children with upper GI bleeding, upper GI endoscopy provides an accurate diagnostic tool and also provides therapeutic intervention when needed